2014
DOI: 10.1103/physrevb.90.064412
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric switchinglike behavior in the magnetoresistance at low fields in bulk metamagnetic Heusler alloys

Abstract: A novel physical phenomenon has been observed that resembles a large asymmetric switching-like magnetoresistance at low applied fields in bulk metamagnetic Heusler alloys.A thermally-activated isothermal forward metamagnetic transition with a signature of a pronounced time-dependent relaxation was observed in a bulk B-substituted off-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[36][37][38] To elucidate the magnetic ground state of any magnetic material, the magnetocaloric effect may be treated as a powerful tool. [39][40][41] The magnetocaloric effect (MCE) is defined by the isothermal magnetic entropy change or adiabatic temperature change of a magnetic material when it is subjected to an external magnetic field. It has been reported that any feeble magnetic transition can be easily detected by the magnetocaloric effect due to its more sensitive nature.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] To elucidate the magnetic ground state of any magnetic material, the magnetocaloric effect may be treated as a powerful tool. [39][40][41] The magnetocaloric effect (MCE) is defined by the isothermal magnetic entropy change or adiabatic temperature change of a magnetic material when it is subjected to an external magnetic field. It has been reported that any feeble magnetic transition can be easily detected by the magnetocaloric effect due to its more sensitive nature.…”
Section: Introductionmentioning
confidence: 99%
“…Ni-Mn-X (X = Sn, In and Sb) metamagnetic shape memory alloys (MSMAs) are of great interests due to their potential applications such as magnetic refrigeration materials, magnetic shape memory effect, magneto-resistance, magneto-thermal conductivity, elasta-caloric effect [1][2][3][4][5][6][7][8][9][10][11]. These alloys are one step ahead in practical applications when considering the cost-performance relationship [12].…”
Section: Introductionmentioning
confidence: 99%
“…The Mn rich off-stoichiometric Ni-Mn-In alloys that undergo a first-order magnetostructural transition near room temperature constitute a class of magnetic materials that is important for both fundamental research and application due to their rich physical properties, such as the metamagnetic shape memory effect [1], giant inverse magnetocaloric effect [2] and giant magnetoresistance effect [3]. However, the relative large hysteresis loss during the magnetostructural transition severely reduces the energy transformation efficiency and then blocks their practical application [4,5].…”
Section: Introductionmentioning
confidence: 99%